Embracing non-tenure track faculty : changing campuses for the new faculty majority - Kezar, Adrianna J. (New York : Routledge, 2012)
'The nature of the higher education faculty workforce has radically and fundamentally changed from primarily full-time, tenured or tenure-track faculty to contingent faculty. Regardless of full or part-time appointments, contingent faculty share a common status: short-tem contracts, lack of job security, lack of a professional career track, and limited support on campus. We know little about efforts to support contingent faculty beyond broad, relatively uninformative survey data. While a few sources have developed recommendations for supporting contingent faculty, no resources have documented the real changes occuring on campuses and the challenges that occur while implementing new policies and practices. Improving Contingent Faculty Relations presents real cases where these new policies and practices have been implemented, unveiling the mechanisms that are required to create change, the challenges and opportunities that implementers face, and how effective methodology depends upon particular campus contexts. Readers will learn the various pathways to new policies and practices and can align their strategies with proven approaches. Contingent faculty contributors document from first-hand experience the change process on their campuses. Kezar supplements these case studies by distilling trends and patterns from a national study of campuses that have successfully implemented policies to improve conditions for nontenure track faculty. This book is essential reading for both contingent faculty and higher education administrators'--
Includes bibliographical references and index.
Keywords: College teachers, Part-time -- United States; College teachers -- Tenure -- United States; Universities and colleges -- United States -- Faculty; College teaching -- United States